2021
DOI: 10.1108/gm-01-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Where is the visible commitment to gender in the advertised content of UK management degree programmes?

Abstract: Purpose The purpose of this paper is to establish the extent to which prospective students can see a visible commitment to study gender in the UK business/management school curriculum prior to enrolment. Design/methodology/approach A content analysis of the descriptions of modules offered as part of business and management degrees offered by 112 UK universities was conducted. The analysis was restricted to the publicly available information on the websites visible to prospective students. Descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Perriton et al’s (2022) article confirmed that these topics remain peripheral, suggesting that students are leaving university without the necessary skills and understanding to perform management roles that challenge rather than reinforce exclusionary stereotypes.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Perriton et al’s (2022) article confirmed that these topics remain peripheral, suggesting that students are leaving university without the necessary skills and understanding to perform management roles that challenge rather than reinforce exclusionary stereotypes.…”
Section: Introductionmentioning
confidence: 83%
“…In HEIs, the silence (or presence) of equality, diversity and inclusion in the curriculum is heavily dependent on the educator/facilitator (Farmer et al, 2018) and other representatives of the business school including the top management, academic administrators and auxiliary staff. The studies by Perriton and Elliott (2018) and Perriton et al (2022) clearly demonstrate that despite the aforementioned formal policy discourse, the actual inclusion of these topics in curricula is very patchy; in many units and modules, they are simply not there, and this 'silence' is itself a message.…”
Section: The Hidden Curriculum Of Equality Diversity and Inclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…We approached this principle based on two baseline assessments: a local level review of problematic or underrepresented visuals (posters, artworks, signage etc.) in the building and published research highlighting gaps in the gender diversity of the UK management curriculum (Perriton and Elliot, 2018; Perriton et al, 2022). These baselines provided justification for staff–student partnerships to improve our physical environment and to raise awareness of, and affect change to, our curriculum.…”
Section: Methodsmentioning
confidence: 99%